Cyclin A2/E1 activation defines a hepatocellular carcinoma subclass with a rearrangement signature of replication stress. Issue 1 (December 2018) - Bayard, Quentin; Meunier, Léa; Peneau, Camille; Renault, Victor; Shinde, Jayendra; Nault, Jean-Charles; Mami, Iadh; Couchy, Gabrielle; Amaddeo, Giuliana; Tubacher, Emmanuel; Bacq, Delphine; Meyer, Vincent; et al.
Abstract Cyclins A2 and E1 regulate the cell cycle by promoting S phase entry and progression. Here, we identify a hepatocellular carcinoma (HCC) subgroup exhibiting cyclin activation through various mechanisms including hepatitis B virus (HBV) and adeno-associated virus type 2 (AAV2) insertions, enhancer hijacking and recurrentCCNA2 fusions. Cyclin A2 or E1 alterations define a homogenous entity of aggressive HCC, mostly developed in non-cirrhotic patients, characterized by a transcriptional activation of E2F and ATR pathways and a high frequency ofRB1 andPTEN inactivation. Cyclin-driven HCC display a unique signature of structural rearrangements with hundreds of tandem duplications and templated insertions frequently activatingTERT promoter. These rearrangements, strongly enriched in early-replicated active chromatin regions, are consistent with a break-induced replication mechanism. Pan-cancer analysis reveals a similar signature inBRCA1 -mutated breast and ovarian cancers. Together, this analysis reveals a new poor prognosis HCC entity and a rearrangement signature related to replication stress. Cyclins A2 and E1 are known to regulate the cell cycle by promoting S phase entry and progression. Here, they identify an aggressive hepatocellular carcinoma subgroup exhibiting cyclin activation through various mechanisms and find this subgroup to display replication stress-induced structural rearrangements frequently activating TERT promoter.